How do travel bloggers influence Generation Z‘s travel decisions? An exploratory study through five Italian famous travel bloggers - Elisa Rancati (European Scientific Journal, ESJ, 2025)
The increasing adoption of new communication channel such as social networks in Generation Z has created new job professional during the last decade: travel bloggers. The aim of this paper is to understand the influence of travel bloggers on Generation Z’s travel decisions. A mixed qualitative and quantitative survey design was employed for this study. Empirical data were drawn from 475 Generation Z’s travellers in Italy, using a purposive sampling technique. The results of this study reveal that travel bloggers for Generation Z’s travel decision making are lightly relevant. This study is amongst the first to empirically investigate the influence of travel bloggers on tourism decision making of Generation Z travellers in the realm of social and mobile business. The paper offers relevant theoretical and managerial implications. First, the paper enriches the travel decision-making Generation Z theory by providing evidence of factors leading to the higher sharing of influence amongst travellers. Second, the paper adds to the literature on Generation Z, demonstrating the individual determinants of influencers sharing videos and photos about products and services in online tourism communities. Thus, building upon the findings of this study, the authors provide some guidelines for travel blogger to promoting destination on social media pages.